Traffic department's order-delivery process optimization and improvement - Luhtanen, Eetu (My University, 2025)
This master's thesis examines the optimization and improvement of the order-delivery process of the traffic department of a Finnish transport and logistics company. The aim of the study is to analyze the current state, identify areas for improvement in the process, and propose improvements that will improve the company's efficiency, reliability, and competitiveness. Additionally, the study develops new performance indicators (KPIs) that can be used to monitor and evaluate the performance of the proposed processes. The research is based on the design science research (DSR) method, which involves developing and testing solutions to the company's operational challenges. Empirical data has been collected through a semi-structured interview with the traffic director, email surveys with traffic managers, and a literature review. In the analysis, process mapping is utilized by using a swimlane diagram, and quantitative methods are employed to measure performance, which include standard deviation, Gini coefficient, MAD (mean absolute deviation), and mean. The results of the study indicate that the current processes of the traffic department contain several areas for improvement, particularly regarding the uneven distribution of resources and unclear customer orders. Improvement proposals include, among other things, centralizing order processing and implementing a standardized order form, which will achieve a more efficient and consistent process. The results of the two-week testing period show that the proposed changes improve resource utilization by approximately 25% and reduce order handling times by about 45%. The conclusions of the study emphasize that a clear process structure and KPI metrics support the continuous improvement and measurement of the traffic department's performance. The proposed improvement suggestions offer concrete solutions for enhancing the company's operations and strengthening its competitiveness. Future research could focus on the broader implementation of the improvement proposals and the assessment of their long-term impact.

Tämä pro gradu -tutkielma tarkastelee suomalaisen kuljetus- ja logistiikka-alan yrityksen liikenneosaston tilaus-toimitusprosessin optimointia ja kehittämistä. Tutkimuksen tavoitteena on analysoida nykytilaa, tunnistaa prosessin kehityskohteet sekä ehdottaa parannuksia, jotka parantavat yrityksen tehokkuutta, toimintavarmuutta ja kilpailukykyä. Lisäksi tutkimuksessa kehitetään uusia suorituskykymittareita (KPI), joiden avulla voidaan seurata ja arvioida ehdotettujen prosessien toimintaa ja tehokkuutta. Tutkimus perustuu design science research (DSR) -menetelmään, jossa kehitetään ja testataan ratkaisuja yrityksen operatiivisiin haasteisiin. Empiirinen aineisto on kerätty liikennejohtajan puolistrukturoidulla haastattelulla, liikennealueiden päälliköiden sähköpostikyselyillä sekä kirjallisuuskatsauksella. Analyysissä hyödynnetään prosessikartoitusta uimaratakaavion avulla, ja suorituskyvyn mittaamiseen käytetään kvantitatiivisia menetelmiä, jotka ovat keskihajonta, Gini-kerroin, MAD (mean absolute deviation) ja keskiarvo. Tutkimuksen tulokset osoittavat, että liikenneosaston nykyiset prosessit sisältävät useita kehityskohteita, erityisesti resurssien epätasaisen jakautumisen ja asiakkaiden epäselvien tilauksien osalta. Kehitysehdotuksina esitetään muun muassa tilauksenkäsittelyn keskittämistä ja standardoidun tilauslomakkeen käyttöönottoa, joiden avulla saavutetaan tehokkaampi ja yhdenmukaisempi prosessi. Kahden viikon testausjakson tulokset osoittavat, että ehdotetut muutokset parantavat resurssien käyttöastetta noin 25 % ja lyhentävät käsittelyaikoja noin 45 %. Tutkimuksen johtopäätökset korostavat, että selkeä prosessirakenne ja KPI-mittarit tukevat liikenneosaston suorituskyvyn jatkuvaa parantamista sekä mittaamista. Esitetyt kehitysehdotukset tarjoavat konkreettisia ratkaisuja yrityksen toiminnan tehostamiseen ja kilpailukyvyn vahvistamiseen. Jatkotutkimuksessa voidaan keskittyä kehitysehdotusten laajempaan käyttöönottoon ja vaikutusten arviointiin pidemmällä aikavälillä.
Keywords: fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management